Evolution of Fungi and Fungal-Like Organisms - Pöggeler, Stefanie; Wöstemeyer, Johannes (The Mycota, A Comprehensive Treatise on Fungi as Experimental Systems for Basic and Applied Research, 2011)
Based on sequence analyses of many different genes, the past decade has provided us with a profound knowledge of fungal systematics and phylogeny. In addition, a number of sequences of complete fungal genomes have been identified and several others will soon follow. In this volume, leading experts address questions concerning the origin of the fungal kingdom and fungal evolution at a level of analytical refinement that has never been possible before. The following major aspects are highlighted: evolutionary roots of fungi; evolution of signaling in fungi and fungal-like organisms; evolution of mutualistic systems and metabolism in fungi; and evolutionary mechanisms and trends.